Straits settlements Blue Book miscellanea (imports/exports) 1885-1886 vol.21-22 (Great Britain : Public Record Office, 1971)
Mengandungi lampiran kepada Straits Settlements. Blue Book for the year 1885;'Blue Book for the year 1886'.